Integrating TOGAF and Big Data for Digital Transformation: Case Study on the Lending Industry - Yudhistira, Andreas; Fajar, Ahmad Nurul (Sinkron : jurnal dan penelitian teknik informatika, 2024)
In today’s digital era, the strategic integration of enterprise architecture frameworks with Big Data technologies is crucial in driving digital transformation, especially within the lending industry. This research aims to identify and analyze how The Open Group Architecture Framework (TOGAF) can be integrated with Big Data to enhance innovation, operational efficiency, and decision-making in the lending sector. This study examines Indonesian financial institutions using qualitative case studies, exploring the intricate practices, challenges, and benefits of the combination of TOGAF and Big Data. The qualitative methodology focuses on in-depth interviews and document analysis to gather contextual insights into the implementation dynamics and impacts of these technologies. Findings indicate that integrating TOGAF and Big Data not only streamlines workflows but also significantly enhances data security and risk management—critical elements in the lending industry. A vital outcome of this study is the development of a robust integration model that serves as a blueprint for companies in similar sectors to navigate their digital transformation journeys. Additionally, this research provides strategic recommendations to overcome integration and implementation challenges. These guidelines facilitate the transition to a more cohesive and strengthened digital architecture, equipping financial institutions to manage the complexities of modern digital economies effectively. Ultimately, this study delivers a comprehensive framework that enriches theoretical understanding and offers practical insights for effective technology integration in financial services.